(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article studies the causes and effects operation of polisemantic features of terminology in the system-structural and cognitive-discursive paradigm. It is revealed that the phenomenon of polisemantic features of linguistic term should be investigated in the sphere of its operation in scientific discourse.